MENINGKATKAN HASIL BELAJAR PADA MATERI HIMPUNAN MENGGUNAKAN PENDEKATAN OPEN ENDED BERBANTUAN VIDEO PEMBELAJARAN SISWA SMP KELAS VII - Frila Delima; Eka Senjayawati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose from research to understand about learning outcomes junior high school student of sets matter. Type of this research is classroom action class and method of research which use is descriptive qualitative. Data collection technique is use five item test question about sets matter ( 1st cycle and 2nd cycle) by using open ended approach to 14 students of class VII-E at SMPN 10 Cimahi and this data processed by using qualitative data processing techniques. The result this classroom action class is post test value of 1st cycle and 2nd cycle activity. Data learning outcomes student of 1st cycle is balance while in 2nd cycle is increase. Because in 2nd cycle is add video learning media about sets matter. Based on the research, can be concluded that learning outcomes student is increase after this classroom action class research implemented.